2005
DOI: 10.1002/jgm.825
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-based defective lentiviral vectors efficiently transduce human monocytes-derived macrophages and suppress replication of wild-type HIV-1

Abstract: Background-Human monocytes play an important role in mediating human immunodeficiency virus type 1 (HIV-1) infection of the central nervous system (CNS), and monocytes-derived macrophages (MDM) represent a major viral reservoir within the brain and other target organs. Current gene transduction of MDM is hindered by a limited efficiency. In this study we established a lentiviral vector-based technique for improved gene transfer into human MDM cultures in vitro and demonstrated significant protection of transdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
4
17
1
Order By: Relevance
“…Overall, these data suggest that the efficiency of DLV-mediated gene transduction in mouse monocytes may be influenced by the extent of cellular differentiation and/or by other changes associated with prolonged in vitro culture. This is consistent with similar observations using primary human monocytes/macrophage cell cultures (Neil et al, 2001;Zeng et al, 2005).…”
Section: Prolonged Time In Culture Results In More Efficient Gene Trasupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, these data suggest that the efficiency of DLV-mediated gene transduction in mouse monocytes may be influenced by the extent of cellular differentiation and/or by other changes associated with prolonged in vitro culture. This is consistent with similar observations using primary human monocytes/macrophage cell cultures (Neil et al, 2001;Zeng et al, 2005).…”
Section: Prolonged Time In Culture Results In More Efficient Gene Trasupporting
confidence: 93%
“…It has recently been demonstrated that primary monocyte cultures isolated from human blood can be efficiently transduced in vitro with HIV-based viral vector pseudotyped with VSV-G envelope and transduced cells maintained an active and long-term reporter gene expression (Zeng et al, 2005). To further investigate the use of the genetically modified monocytes/ macrophages in gene therapy for the central nervous system, it is of importance to establish an experimental model system to test the efficacy of monocyte trafficking into the brain and the efficiency of target gene expression in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV-based lentivirus stocks were generated by transient plasmid transfection into 293T cells as described previously 19). PRx1 cDNA was amplified using 5'-CGCGAATTCATGTCTTCAGGAAATGCA-3' and 5'-CGCCTCGAGTCACTTCTGCTTAGAGAA-3' using Taq polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…Scientists are already overcoming the problems of insufficient gene transduction by using novel constructs [49] or by switching to lentiviral-mediated transduction [50,51]. The first clinical trial using lentiviral vectors in HIV-positive patients began in 2001, and results will be forthcoming [52].…”
Section: Resultsmentioning
confidence: 99%